Prognostic value of PCT, copeptin, MR-proADM, MR-proANP and CT-proET-1 for severe acute dyspnea in the emergency department: the BIODINER study. (2nd January 2017) - Hausfater, Pierre; Claessens, Yann-Erick; Martinage, Arnaud; Joly, Luc-Marie; Lardeur, Jean-Yves; Der Sahakian, Guillaume; Lemanski, Claire; Ray, Patrick; Freund, Yonathan; Riou, Bruno
Abstract: Context: Acute dyspnea is a frequent complaint in patients attending the emergency department (ED). Objective: To evaluate the accuracy of PCT, MR-proANP, MR-proADM, copeptin and CT-proET1 for the risk-stratification of severe acute dyspnea patients presenting to the ED. Methods: Multicenter prospective study in adult patients with a chief complaint of acute dyspnea. Pro-hormone type biomarkers concentrations were measured on arrival. Combined primary endpoint was a poor outcome. Results: Three hundred and ninety-four patients were included, 137 (35%) met the primary endpoint. MR-proADM was the only biomarker associated with the primary endpoint (odds ratio 1.43 [95%CI: 1.13–1.82], p = 0.003) as were the presence of paradoxical abdominal breathing (odds ratio 2.48 [95%CI: 1.31–4.68]) or cyanosis (odds ratio 3.18 [1.46–6.89]) Conclusions: In patients with severe acute dyspnea in the ED, pro-hormone type biomarkers measurements have a low added value to clinical signs for the prediction of poor outcome.